High-starchy carbohydrate diet aggravates NAFLD by increasing fatty acids influx mediated by NOX2 - Yuqi Gao; Rui Hua; Kezheng Peng; Yuemiao Yin; Chenye Zeng; Yannan Guo; Yida Wang; Liyuan Li; Xue Li; Ying Qiu; Zhao Wang (Food Science and Human Wellness)
Nonalcoholic fatty liver disease (NAFLD) is a high-incidence lipid disorder that affects more than a quarter of the population worldwide, and dietary intervention is the recognized treatment. Starch is the main component of staple foods that are consumed daily, and the effects, metabolic pathway, and molecular mechanism of starch in the context of NAFLD remain unclear. Our study showed that a high-starch carbohydrate diet (HCD) led to the occurrence and exacerbation of NAFLD in mice. Transcriptomics and metabonomic analyses showed that the increased fatty acid influx mediated by NADPH oxidase 2 (NOX2) exacerbated NAFLD. Knocking down NOX2 specifically alleviated HCD-induced NAFLD in vivo and in vitro. Moreover, the large amounts of ROS produced by NOX2 further exacerbated insulin resistance and increased lipolysis in perirenal white adipose tissue (periWAT), thereby providing fatty acids for hepatic lipid synthesis. In addition, the interaction between AMPKα1 and p47phox was the pathway that mediated the high expression of NOX2 induced by a HCD. Our study systematically demonstrated the effect of a HCD on NAFLD. Elevated fatty acid influx is a unique molecular regulatory pathway that mediates HCD-induced NAFLD exacerbation, which is different from the effect of simple sugars. Additionally, NOX2 was suggested to be a specific and effective drug target for NAFLD.